1981
DOI: 10.1037/0033-2909.90.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic variations and visual information processing.

Abstract: Based upon an analysis of how graphemic symbols are mapped onto spoken languages, three distinctive writing systems with three different relations between script and speech relationships are identified.They are logography, syllabary, and alphabet, developed sequentially in the history of mankind. It is noted that this trend of development seems to coincide with the trend of cognitive development of children. This coincidence may imply that different cognitive processes are required for achieving reading profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 122 publications
(161 reference statements)
2
84
0
1
Order By: Relevance
“…Referring to the experimental data on the inhibition and facilitation of the phonological radical of bi-part character according to tasks, and the consistent frequency effect, phonological activation is primary, but lexical process is inevitable. Some studies concluded the primacy of phonological activation (e.g., Chen et al 1988, Hoosain andOsgood 1983;Jin 2013;Hung and Tzeng 1981;Peng et al 1985), and other studies remained to insist the lexical process is inevitable with Chinese (Baron and Strawson 1976;Leong 1986;Mattingly 1992). However, this study confirmed both the primacy of phonological process even in the semantically related tasks, and the inevitability of lexical process even in phonologically related tasks.…”
Section: Suggestion and Conclusionmentioning
confidence: 43%
“…Referring to the experimental data on the inhibition and facilitation of the phonological radical of bi-part character according to tasks, and the consistent frequency effect, phonological activation is primary, but lexical process is inevitable. Some studies concluded the primacy of phonological activation (e.g., Chen et al 1988, Hoosain andOsgood 1983;Jin 2013;Hung and Tzeng 1981;Peng et al 1985), and other studies remained to insist the lexical process is inevitable with Chinese (Baron and Strawson 1976;Leong 1986;Mattingly 1992). However, this study confirmed both the primacy of phonological process even in the semantically related tasks, and the inevitability of lexical process even in phonologically related tasks.…”
Section: Suggestion and Conclusionmentioning
confidence: 43%
“…However, later research (e.g., Hung & Tzeng, 1981;Tzeng et al, 1977) strongly suggested that processing of…”
Section: Discussionmentioning
confidence: 99%
“…Writing systems differ in the manner in which they represent phonological information (Henderson, 1982;Hung & Tzeng, 1981;Rozin & Gleitman, 1977). As a consequence, there are variations between orthographies in the extent to which written words represent their pronunciations.…”
mentioning
confidence: 99%
“…Because written English is based on an alphabetic principle, a skilled reader is likely to be able to pronounce correctly an unfamiliar word the first time it is seen. In Chinese, which is logographic, only a small proportion of characters represent phonological information, making it difficult for even a skilled reader to pronounce correctly an unfamiliar character (Hung & Tzeng, 1981). Orthographies have evolved toward a more direct representation of phonology, a fact that would be difficult to explain unless phonological information had a role in either skilled reading or learning to read.…”
mentioning
confidence: 99%
See 1 more Smart Citation